ClojureScript: Functional Programming for JavaScript Platforms - McGranaghan, M. (IEEE internet computing, 2011)
ClojureScript is a compiler from a Clojure-like functional programming language to JavaScript. ClojureScript features deep integration with the Google Closure JavaScript library and whole-program optimizing compiler. ClojureScript brings efficient functional programming to JavaScript environments such as the browser, which are becoming increasingly important components of full-stack Web applications.